A case of community-based fall prevention: Survey of organization and content of minor home help services in Swedish municipalities. Issue 7 (November 2014) - Bernfort, Lars; Eckard, Nathalie; Husberg, Magnus; Alwin, Jenny
Background: The aim of this study was to survey minor home help services provided by Swedish municipalities with the main purpose to prevent fall injuries. Methods : If minor home help services were presented on the homepage of a municipality, an initial telephone contact was taken. Thereafter a questionnaire was administered, including questions about target groups, aim with the services, tasks included, costs and restrictions for users, budget, and experienced gains with the services. Municipalities not providing minor home help services were asked about the reason therefore and if the municipality had previously provided the services Results : The questionnaire response rate was 92%. In 191 of Sweden's 290 municipalities services were provided by, or in cooperation with, the municipality. Reasons for not providing the services were mainly financial and lack of demand. Services were more often provided in larger cities and in municipalities located in populous regions. In some municipalities services were performed by persons with functional disabilities or unemployed persons. Conclusions : Both providers and users expressed satisfaction with the services. Aspects expressed were that services lead to greater sense of safety and social gains. The effect of the services in terms of fall prevention is yet to be proved. With only a small fall-preventive effect services are probably cost-effective. Improved quality of life, sense of safety, and being able to offer meaningful work to otherwise unemployed persons are important aspects that might in themselves motivate the provision of minor home help services.